Consumption of added fats and oils in the European Prospective Investigation into Cancer and Nutrition (EPIC) centres across 10 European countries as assessed by 24-hour dietary recalls - Linseisen, J; Bergström, E; Gafá, L; González, C; Thiébaut, A; Trichopoulou, A; Tumino, R; Sánchez, C; Garcia, C; Mattisson, I; Nilsson, S; Welch, A; et al. (2002)
Objective: To evaluate the consumption of added fats and oils across the European centres and countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC). Design and setting: 24-Hour dietary recalls were collected by means of standardized computer-guided interviews in 27 redefined EPIC centres across 10 European countries. Subjects: From an initial number of 36 900 subjects, single dietary recalls from 22 924 women and 13 031 men in the age range of 35-74 years were included. Results: Mean daily intake of added fats and oils varied between 16.2 g (Varese, Italy) and 41.1 g (Malmö, Sweden) in women and between 24.7 g (Ragusa, Italy) and 66.0 g (Potsdam, Germany) in men. Total mean lipid intake by consumption of added fats and oils, including those used for sauce preparation, ranged between 18.3 (Norway) and 37.2g day-1 (Greece) in women and 28.4 (Heidelberg, Germany) and 51.2g day-1 (Greece) in men. The Mediterranean EPIC centres with high olive oil consumption combined with low animal fat intake contrasted with the central and northern European centres where fewer vegetable oils, more animal fats and a high proportion of margarine were consumed. The consumption of added fats and oils of animal origin was highest in the German EPIC centres, followed by the French. The contribution of added fats and oils to total energy intake ranged from 8% in Norway to 22% in Greece. Conclusions: The results demonstrate a high variation in dietary intake of added fats and oils in EPIC, providing a good opportunity to elucidate the role of dietary fats in cancer aetiology.